2019
DOI: 10.1109/jphot.2019.2950021
|View full text |Cite
|
Sign up to set email alerts
|

Active Terahertz Polarization Converter Using a Liquid Crystal-Embedded Metal Mesh

Abstract: We report a terahertz (THz) metamaterial consisting of a metal mesh layer with nematic liquid crystals (LCs). The metal mesh has subwavelength apertures that function as a bandpass filter in the THz spectral range. The LCs are embedded and aligned homogeneously in the apertures. The electromagnetic characteristics were calculated with a finite-difference time-domain method. The metamaterial converts the polarization of the THz wave during transmission and the thickness of the LC layer can be reduced by two ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…The free control of liquid crystal orientation can promote the development of manipulability of metamaterial-based devices. Based on the tunability of the refractive index of liquid crystal, more latent applications of liquid crystal background metamaterials have been discussed such as the perfect absorber [62,70,106,107], polarization converter [108,109], and modulators [110][111][112][113]. Salvatore Savo et al have illustrated the ability of functional liquid crystals in a metamaterial absorber array working as a spatial light modulator during THz wavelengths by experiments.…”
Section: Liquid Crystals-based Applicationsmentioning
confidence: 99%
“…The free control of liquid crystal orientation can promote the development of manipulability of metamaterial-based devices. Based on the tunability of the refractive index of liquid crystal, more latent applications of liquid crystal background metamaterials have been discussed such as the perfect absorber [62,70,106,107], polarization converter [108,109], and modulators [110][111][112][113]. Salvatore Savo et al have illustrated the ability of functional liquid crystals in a metamaterial absorber array working as a spatial light modulator during THz wavelengths by experiments.…”
Section: Liquid Crystals-based Applicationsmentioning
confidence: 99%
“…Metasurfaces are artificial two-dimensional periodic structures composed of several subwavelength cells arranged in a planar array [ 20 ]. By optimizing the size, structure and periodicity of cells, the metasurface with different electromagnetic properties can be obtained, further realizing the regulation of amplitude and phase of the electromagnetic waves [ 21 , 22 ]. Metasurface absorbers for bi-material micro-cantilever terahertz detectors are required to obtain high absorptivity and significant photothermal responsivity to meet the demand of high-sensitivity detection [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we proposed a THz metasurface consisting of a nematic LC and a subwavelength metal mesh [24]. Metal meshes with subwavelength apertures exhibit extraordinary transmission, and they have been used as frequency selective surfaces (FSSs), such as THz bandpass filters [25][27].…”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary transmission in the THz spectral range is generally explained by a coupled-mode model of spoof surface plasmon polaritons [28]. In our previous study, based on experiments and numerical simulations, we demonstrated that the LC metasurface converts the polarization state of the THz wave in the transmission process and the thickness of the LC layer can be reduced by two orders of magnitude relative to the planarly aligned LC without metal meshes [24]. As mentioned above, this is an advantage for the response speed in active control.…”
Section: Introductionmentioning
confidence: 99%